Selected class I and class II HLA alleles and haplotypes and risk of high‐grade cervical intraepithelial neoplasia - Ades, Steven; Koushik, Anita; Duarte‐Franco, Eliane; Mansour, Nabil; Arseneau, Jocelyne; Provencher, Diane; Gilbert, Lucy; Gotlieb, Walter; Ferenczy, Alex; Coutlée, François; Roger, Michel; Franco, Eduardo L. (International journal of cancer, 2008)
Human leukocyte antigens (HLAs) present foreign antigens to the immune system and may be important determinants of cervical neoplasia. Previously published associations between HLA and cervical neoplasia exhibit considerable variation in findings. The biomarkers of cervical cancer risk (BCCR) case‐control study addressed the role of specific HLA alleles as cofactors in the development of high‐grade cervical intraepithelial neoplasia (HG‐CIN) based on the most consistent evidence from published literature. Cases (N = 381) were women with histologically‐confirmed HG‐CIN attending colposcopy clinics and controls (N = 884) were women from outpatient clinics with normal cytological screening smears. Subjects were mainly of French‐Canadian descent. Cervical specimens were tested for human papillomavirus (HPV) DNA and HLA genotypes by PGMY L1 consensus primer PCR and a PCR sequence‐specific primer method, respectively. Unlike other studies, the DQB1*03 and DRB1*13 allele groups were not associated with risk of HG‐CIN. The B7‐DRB1*1501‐DQB1*0602 haplotype was associated with a 41% overall reduction in HG‐CIN risk (odds ratio [OR] = 0.59; 95% confidence interval [CI]: 0.36–0.96), and an 83% reduction in risk of HG‐CIN among HPV 16 or HPV 18‐positive subjects (OR = 0.17; 95%CI: 0.05–0.54). Paradoxically, however, the same haplotype was associated with HPV 16/18 infection risk among controls (OR = 8.44, 95%CI: 1.12–63.73). In conclusion, the B7‐DRB1*1501‐DQB1*0602 haplotype was protective against HG‐CIN, especially in individuals infected with oncogenic HPV, but the mechanism of the association seems to involve multiple steps in the natural history of HPV and CIN. © 2008 Wiley‐Liss, Inc.